ChemInform Abstract: Metal‐Organic Frameworks Based Upon Non‐zeotype 4‐Connected Topology. Issue 16 (22nd April 2014) - Li, Dong‐Sheng; Wu, Ya‐Pan; Zhao, Jun; Zhang, Jian; Lu, Jack Y.
Abstract Review: 189 refs.